Pain Perception and Anxiety Levels during Menstrual Cycle Associated with Periodontal Therapy - Nikhat Fatima; P. Raja Babu; Vidya Sagar Sisinty; Bassel Tarakji (Hindawi Limited, 2014)
Objectives. To compare the pain perception and anxiety levels of female patients undergoing scaling and root planing during menstrual (perimenstrual) period with those observed during postmenstrual period. Materials and Methods. This was a single blind study, with a split-mouth design. Forty-four women with chronic periodontitis with regular menstrual cycles were subjected to complete Corah's Dental Anxiety Scale (DAS) during their first debridement visit. Patients were randomly selected to undergo their first debridement visit during either their menstrual or postmenstrual period. Scaling was performed under local anesthesia in bilateral quadrants of patients during the periods. Visual Analogue Scale (VAS) was used to score pain levels for each quadrant after performing scaling and root planing. Results. Increase in pain perception among females during their menstrual or perimenstrual period was significantly greater than their postmenstrual period (P < 0.05). It is observed that women whose first appointment was given in perimenstrual period had more pain (VAS) (P = 0.0000) when compared to those women whose first appointment was given in postmenstrual period. Conclusion. Females in their menstrual period demonstrated higher pain responses and high anxiety levels to supra- and subgingival debridement. This increase in the pain levels of women during their menstrual period was statistically significant. If the appointments are given in postmenstrual period, women feel less pain.